2003
DOI: 10.1073/pnas.0534231100
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin-coated pits with long, dynamin-wrapped necks upon expression of a clathrin antisense RNA

Abstract: To investigate the role of clathrin in coated vesicle formation, a cell line with inducible expression of clathrin heavy chain (CHC) antisense RNA was produced. After 18 h of CHC antisense RNA expression, the internalization of transferrin was inhibited by 90%. Although the amount of CHC was reduced by only 10%, the frequency of clathrin-coated pits at the cell surface increased by a factor of 3-5, and clathrin-coated structures also accumulated on a pleiomorphic, multivesicular, endosomal compartment. Remarka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
56
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 26 publications
6
56
2
Order By: Relevance
“…These data indicate that siRNA treatment against clathrin led to a modest decrease in the total amount of dynamin per cell ( Figure 2C). The lack of increase in cellular dynamin in response to clathrin depletion is in contrast to a recently published report in another cell line using an alternative approach to reduce the cellular abundance of clathrin (Iversen et al, 2003). A similar analysis indicated that the average AP-2 immunostaining per cell, as well as the total number of AP-2 assemblies showed a modest increase.…”
Section: Targeted Reduction In Clathrin Heavy and Light Chainscontrasting
confidence: 71%
“…These data indicate that siRNA treatment against clathrin led to a modest decrease in the total amount of dynamin per cell ( Figure 2C). The lack of increase in cellular dynamin in response to clathrin depletion is in contrast to a recently published report in another cell line using an alternative approach to reduce the cellular abundance of clathrin (Iversen et al, 2003). A similar analysis indicated that the average AP-2 immunostaining per cell, as well as the total number of AP-2 assemblies showed a modest increase.…”
Section: Targeted Reduction In Clathrin Heavy and Light Chainscontrasting
confidence: 71%
“…Interestingly, the expression level of clathrin heavy chain was found to be downregulated both at the mRNA and protein levels. The concomitant increase of dynamin and decrease of clathrin expression may be explained by the recent results from Iversen et al (2003) showing that a downregulation of clathrin induced an upregulation of dynamin in fibroblasts. These modulations resulted in an accumulation of clathrin-coated pits at the cell surface connected to the plasma membrane via long dynaminwrapped necks (Iversen et al, 2003).…”
Section: Discussionmentioning
confidence: 94%
“…The concomitant increase of dynamin and decrease of clathrin expression may be explained by the recent results from Iversen et al (2003) showing that a downregulation of clathrin induced an upregulation of dynamin in fibroblasts. These modulations resulted in an accumulation of clathrin-coated pits at the cell surface connected to the plasma membrane via long dynaminwrapped necks (Iversen et al, 2003). Taken together, these results suggest that chronic morphine treatment alters membrane and probably receptors trafficking in rat striatum.…”
Section: Discussionmentioning
confidence: 94%
“…Self-assembly can stimulate dynamin GTPase activity as much as 100-fold (6). Dynamin spirals similar in dimensions to those formed in vitro can be detected as electron dense collars around the elongated necks of endocytic intermediates that accumulate in mammalian cells when clathrinmediated endocytosis is inhibited by perturbing dynamin (7) or clathrin (8) function. Recently, it has been shown that overexpression of an assembly-defective dynamin mutant blocks clathrin-mediated endocytosis (9), confirming that dynamin self-assembly is required.…”
mentioning
confidence: 96%